2002
DOI: 10.1099/00221287-148-3-685
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gluconeogenic and anaplerotic enzymes in Campylobacter jejuni: an essential role for phosphoenolpyruvate carboxykinase

Abstract: Campylobacter jejuni is unable to utilize glucose as a carbon source due to the absence of the key glycolytic enzyme 6-phosphofructokinase. The genome sequence of C. jejuni NCTC 11168 indicates that homologues of all the appropriate enzymes for gluconeogenesis from phosphoenolpyruvate (PEP) are present, in addition to the anaplerotic enzymes pyruvate carboxylase (PYC), phosphoenolpyruvate carboxykinase (PCK) and malic enzyme (MEZ). Surprisingly, a pyruvate kinase (PYK) homologue is also present. To ascertain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
128
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(134 citation statements)
references
References 27 publications
6
128
0
Order By: Relevance
“…The carbon sources that C. jejuni can utilize in the chicken cecum are unknown, although the most likely source of carbon and nitrogen in vivo is via deamination of amino acids, given that C. jejuni is asaccharolytic (41). In previous studies, in vitro experiments have shown that C. jejuni can grow in minimal media by using serine, aspartate, glutamate, and proline as carbon sources (20).…”
Section: ϫ7mentioning
confidence: 99%
“…The carbon sources that C. jejuni can utilize in the chicken cecum are unknown, although the most likely source of carbon and nitrogen in vivo is via deamination of amino acids, given that C. jejuni is asaccharolytic (41). In previous studies, in vitro experiments have shown that C. jejuni can grow in minimal media by using serine, aspartate, glutamate, and proline as carbon sources (20).…”
Section: ϫ7mentioning
confidence: 99%
“…Within those natural habitats, C. jejuni is able to metabolize products like free amino and keto acids generated by these accompanying bacterial species or from the host itself (Lee & Newell, 2006). Since C. jejuni lacks the glycolytic enzyme phosphofructokinase, glucose cannot be catabolized, and other products serve as electron donors for respiration, for instance succinate, malate, formate, Dlactate, hydrogen and NAD(P)H (Hoffman & Goodman, 1982;Parkhill et al, 2000;Kelly, 2001;Sellars et al, 2002;Velayudhan & Kelly, 2002). It has also been shown that sulphite can be exploited as a respiratory electron donor.…”
Section: Introductionmentioning
confidence: 99%
“…The microaerophilic nature, complex nutritional requirements and relative difficulty of culturing C. jejuni have all contributed to the limited understanding of metabolism (Kelly, 2001(Kelly, , 2005Sellars et al, 2002). C. jejuni is unable to catabolize glucose and other hexose sugars due to the absence of the key glycolytic enzyme 6-phosphofructokinase (Parkhill et al, 2000;Velayudhan & Kelly, 2002 The importance of each amino acid in C. jejuni metabolism is yet to be fully established, however, and information on the carbon and nitrogen flow in this organism remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…The microaerophilic nature, complex nutritional requirements and relative difficulty of culturing C. jejuni have all contributed to the limited understanding of metabolism (Kelly, 2001(Kelly, , 2005Sellars et al, 2002). C. jejuni is unable to catabolize glucose and other hexose sugars due to the absence of the key glycolytic enzyme 6-phosphofructokinase (Parkhill et al, 2000;Velayudhan & Kelly, 2002). Amino acids serve as major substrates for C. jejuni, and molecular detail concerning the utilization of L-serine, L-aspartate, L-proline and L-glutamate has begun to emerge (Guccione et al, 2008;Joshua et al, 2006;Kelly, 2005;Leach et al, 1997;Del Recio Leon-Kempis et al, 2006;Velayudhan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation